LEVERAGE DAN OPINI AUDIT GOING CONCERN - Kaihatu Bryan Petrus; Christine Novita Dewi (Fakultas Bisnis UKDW, 2016)
The purpose of this research is to examine and analyse the impact of leverage towards acceptance ofaudit opinion going concern. Population of this research is manufacturing company listing inIndonesia Stock Exchange (BEI) during 2004-2013. From total 125 manufacturing companies, thereare only 31 companies that fulfill criteria of research sample. This research is using audited financialreport to determine whether company received going concern opinion or not. The result shows thatleverage has significantly positive impact to audit report-going concern. The increase of debt toequity ratio, the more potential company receives audit going concern opinion. This result becomesstronger when the company is audited by bigfour.Keywords: Leverage, Audit Opinion, Going Concern, Big Four